Knowledge Modeling of Inquiry-based Learning Using Ontology in Japanese High Schools: Construction of PPDAC Cycle Ontology - Hayashi, Hiroki; Sasajima, Munehiko (Transactions of the Japanese Society for Artificial Intelligence, 2025)
The purpose of this study is to clarify the overall framework of Inquiry based learning in Japanese high schoolsthrough knowledge modeling using ontology. Recently, inquiry-based learning (IBL), which aims at solving problems,has become popular in Japanese high school education. However, because of no teachers specializing in IBLand no textbooks, there is a lack of teaching resources. One solution to the problem is to conduct knowledge modelingas alternative to textbooks. This study proposes the Problem-Plan-Data-Analysis-Conclusion cycle (PPDAC cycle)ontology for use in teaching IBL. The PPDAC cycle is one of the statistical problem-solving processes. As a result ofthis study, we were able to construct a knowledge model that clarifies the overall framework of IBL. We verified thatits impact can contribute to improving the instructional skills of teachers with inexperience in teaching. The futureprospect is to develop an instructional advisory support system for inquiry-based learning. This paper is a study ofthe initial stage of system development.